2022
DOI: 10.3390/antibiotics11111468
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomics Used to Describe the Chemical Composition, Antioxidant and Antimicrobial Effects of Extracts from Pleurotus spp. Mycelium Grown in Different Culture Media

Abstract: Pleurotus species isolated in vitro were studied to determine the effect of different media on their production of secondary metabolites, antimicrobial, and antioxidant activity. The different metabolites among Pleurotus samples covered a total of 58 pathways. Comparisons were made between the metabolic profiles of Pleurotus spp. mycelia grown in two substrates: Potato-dextrose-agar-PDA, used as control (S1), and PDA enriched with 0.5 % of wheat straw (S2). The main finding was that the metabolic pathways are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…TPC values ranged from 38.5 to 423.7 mg GAE/100 g and were all lower than those reported in this paper. Concerning antioxidant properties, Ianni et al [ 22 ] reported a wide range for FRAP (6.0–70.0 mg TE/100 g value) and DPPH (8.7 to 172.0 mg TE/100 g) values, which are all lower than those obtained for F. officinalis, while ABTS values (110.7–1112.7 mg TE/100 g) were similar or lower, a comparison of the antioxidant assay results with those in the literature was sometimes not possible because the data of these assays were reported as EC 50 or radical scavenging activity (%) [ 11 , 19 , 23 , 24 , 25 ]. A correlation study was also conducted considering all the extracts and all spectrophotometric parameters ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…TPC values ranged from 38.5 to 423.7 mg GAE/100 g and were all lower than those reported in this paper. Concerning antioxidant properties, Ianni et al [ 22 ] reported a wide range for FRAP (6.0–70.0 mg TE/100 g value) and DPPH (8.7 to 172.0 mg TE/100 g) values, which are all lower than those obtained for F. officinalis, while ABTS values (110.7–1112.7 mg TE/100 g) were similar or lower, a comparison of the antioxidant assay results with those in the literature was sometimes not possible because the data of these assays were reported as EC 50 or radical scavenging activity (%) [ 11 , 19 , 23 , 24 , 25 ]. A correlation study was also conducted considering all the extracts and all spectrophotometric parameters ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ciprofloxacin (Sigma, Germany) was used in the range of 0.12–125 −1 µg/mL as a control antibacterial agent [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations